A Case of Duodenal Bleeding in a One-Year-Old Child in the Early Postoperative Period after the Surgical Correction of Congenital Heart Defect - Tsymbal, Olena I.; Boyko, Serhii M. (Ukrainian Journal of Cardiovascular Surgery, 2023)
Background. Gastrointestinal bleeding in children is a rather rare pathology. This especially applies to the bleeding in the postoperative period after surgical interventions that are not related to the pathology of the gastrointestinal tract. As a result, clinicians are not alert to the occurrence of such complications, which, in turn, can lead to late diagnosis and delay in the treatment of bleeding. Case report. We present a clinical case of duodenal bleeding in a one-year-old child in the early postoperative period after radical repair of ventricular septal defect by patching the defect. Laboratory parameters on admission: hemoglobin 120 g/L, red blood cells 4.37×1012/L. On the first postoperative day, hemoglobin was 103 g/L, hematocrit was 33%. On the 5th day after the operation, the boy had a currant jelly stool. Hemostatic therapy was provided: transfusion of fresh frozen plasma at a dose of 10 mL/kg, single administration of tranexamic acid at a dose of 10 mg/kg. The bleeding was stopped. After hemostatic therapy, hemoglobin was 105 g/L, hematocrit was 31%. Within 24 hours, fibrogastroduode-noscopy was performed which revealed an ulcer of the duodenal bulb covered with fibrin. The boy was consulted by gastroenterologist. Pathogenetic therapy was prescribed: proton pump inhibitors, antacids, enveloping drugs. The child was discharged home in a satisfactory condition on the 15th day after the operation under the supervision of a district pediatrician, cardiologist, and gastroenterologist. Laboratory parameters at discharge: hemoglobin 91 g/L, red blood cells 3.3×1012/L. Conclusion. The problem of gastrointestinal complications, including gastrointestinal bleeding in young children af-ter cardiac surgery, is extremely insufficiently covered in the scientific literature. Many questions remain unsolved re-garding the prevention, early diagnosis and treatment of bleeding, so research in this field remains relevant for both clinicians and scientists.